Damage on intestinal barrier function and microbial detoxification of deoxynivalenol: A review - Jia Chen; Xinran Zhang; Ziqi He; Dongwei Xiong; Miao Long (Journal of Integrative Agriculture, 2024)
Deoxynivalenol (DON) is a mycotoxin that is produced by various species of Fusarium and is ubiquitous in food and feed. At low concentrations, it can cause metabolic disorders in animals and humans and, at high concentrations, it can lead to pathological changes in the body. The impact of DON on human/animal health and animal productivity has thus attracted a great deal of attention around the world. DON causes severe damage to the intestine, including compromised intestinal barrier, mucosal damage, weakened immune function, and alterations in gut microbiota composition. These effects exacerbate intestinal infections and inflammation in livestock and poultry, posing adverse effects on overall health. Furthermore, research into biological methods for DON detoxification is a crucial avenue for future studies. This includes the utilization of adsorption, enzymatic degradation, and other biological approaches to mitigate DON’s impact, offering new strategies for prevention and treatment of DON-induced diseases. Future research will focus on identifying highly efficient detoxifying microorganisms or enzymes to reduce DON levels in food and feed, thereby mitigating its risks to both animals and human health.